2008
DOI: 10.1186/1471-2180-8-118
|View full text |Cite
|
Sign up to set email alerts
|

A dengue receptor as possible genetic marker of vector competence in Aedes aegypti

Abstract: Background: Vector competence refers to the intrinsic permissiveness of an arthropod vector for infection, replication and transmission of a virus. Notwithstanding studies of Quantitative Trait Loci (QTL) that influence the ability of Aedes aegypti midgut (MG) to become infected with dengue virus (DENV), no study to date has been undertaken to identify genetic markers of vector competence. Furthermore, it is known that mosquito populations differ greatly in their susceptibility to flaviviruses. Differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 53 publications
1
48
0
2
Order By: Relevance
“…Vector competence, which is the capacity of an arthropod to acquire an infection and transmit it to a subsequent host, can greatly vary among individuals and between populations (Lorenz et al 1984, Turell et al 1992 and is influenced by genetics (Mercado-Curiel et al 2008) as well as by climate variables, such as temperature (Davis 1932, Turell 1993, Dohm et al 2002). An increase in environmental temperature for adult mosquitoes reduces the EIP (Davis 1932, Chamberlain andSudia 1955), most likely due to an increase in the metabolism of the adult mosquito and the replication speed of the virus.…”
Section: Introductionmentioning
confidence: 99%
“…Vector competence, which is the capacity of an arthropod to acquire an infection and transmit it to a subsequent host, can greatly vary among individuals and between populations (Lorenz et al 1984, Turell et al 1992 and is influenced by genetics (Mercado-Curiel et al 2008) as well as by climate variables, such as temperature (Davis 1932, Turell 1993, Dohm et al 2002). An increase in environmental temperature for adult mosquitoes reduces the EIP (Davis 1932, Chamberlain andSudia 1955), most likely due to an increase in the metabolism of the adult mosquito and the replication speed of the virus.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent studies have shown that an individual mosquito’s susceptibility to infection with a pathogen can be affected by small changes in environmental factors (e.g., Kilpatrick et al 2008, Richards et al 2009) and within-individual factors (e.g., binding of viruses to midgut proteins, Mercado-Curiel et al 2008), likely influencing population- and species-level variation in vector competence. However, how this individual variation affects transmission dynamics beyond the individual level is not known.…”
mentioning
confidence: 99%
“…Interestingly, the presence of the 67 kDa protein in midgut cells of three varieties of Ae. aegypti mosquitoes correlated with their susceptibility to DENV infection, thus, it has been proposed as a vector competence marker [95]. Finally, proteins ranging in molecular weight from 77 to 37 kDa obtained from Ae.…”
Section: Dengue Virus Receptors In Mosquitoesmentioning
confidence: 99%